2011
DOI: 10.1245/s10434-011-1976-9
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Prognostic Factor among Patients with Stage III Melanoma

Abstract: Decreased psoas muscle density on CT, an objective measure of frailty, was as important a predictor of outcome as tumor factors in a cohort of stage III melanoma patients. On multivariate analysis, frailty, not age, was associated with decreased disease-free survival and distant disease-free survival, and higher rate of surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
203
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(223 citation statements)
references
References 30 publications
15
203
2
3
Order By: Relevance
“…Importantly, low muscle radiodensity is emerging as an important and in some cases stronger predictor of clinical outcomes (compared with muscle mass alone). In Sabel et al (60) low (psoas) muscle radiodensity was associated with disease-free and distant disease-free survival (P = 0·04 and P = 0·0002, respectively). These results were supported by a Martin et al (20) study, where low muscle attenuation was a powerful predictor of survival (HR 1·36, 95 % CI 1·2, 1·6), and more recently by Okumura et al (50) , who showed low muscle quality associated with poor overall (HR 2·5, P < 0·001) and recurrence free (HR 1·6; P = 0·004) survival.…”
Section: Impact Of Muscle Radiodensitymentioning
confidence: 88%
“…Importantly, low muscle radiodensity is emerging as an important and in some cases stronger predictor of clinical outcomes (compared with muscle mass alone). In Sabel et al (60) low (psoas) muscle radiodensity was associated with disease-free and distant disease-free survival (P = 0·04 and P = 0·0002, respectively). These results were supported by a Martin et al (20) study, where low muscle attenuation was a powerful predictor of survival (HR 1·36, 95 % CI 1·2, 1·6), and more recently by Okumura et al (50) , who showed low muscle quality associated with poor overall (HR 2·5, P < 0·001) and recurrence free (HR 1·6; P = 0·004) survival.…”
Section: Impact Of Muscle Radiodensitymentioning
confidence: 88%
“…Higher skeletal muscle density has been associated with improved survival in renal cell carcinoma (38) , melanoma (68) and in a number of others solid tumours (42) . Skeletal muscle density could potentially be a more accurate measure of muscle function and therefore precede the development of sarcopenia.…”
Section: Impact Of Sarcopenia On Tolerance To Cytotoxic Chemotherapymentioning
confidence: 99%
“…[3,4] There is also evidence to suggest a significant correlation with long-term outcomes after cancer resection. [5,6] Importantly, sarcopenia increases with advanced age, where the propensity for poor surgical outcomes is well-established. Nonetheless, there is evidence to suggest that sarcopenia may be at least partially independent from age and comorbid disease burden as a domain of surgical risk.…”
Section: Introductionmentioning
confidence: 99%